2017
DOI: 10.1136/bmjopen-2017-016321
|View full text |Cite
|
Sign up to set email alerts
|

Is local anaesthesia a favourable approach for transcatheter aortic valve implantation? A systematic review and meta-analysis comparing local and general anaesthesia

Abstract: ObjectivesWe conducted a systematic review and meta-analysis to identify the potential favourable effects of local anaesthesia plus sedation (LAS) compared with general anaesthesia (GA) in transcatheter aortic valve implantation (TAVI).MethodsElectronic databases (PubMed/Medline, Embase, Cochrane Central Register of Controlled Trials) and the reference lists of eligible publications were screened for randomised controlled trials (RCTs) and observational studies published between 1 January 2006 and 26 June 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 49 publications
(54 reference statements)
3
32
1
2
Order By: Relevance
“…Fröhlich et al in a meta‐analysis described the conversion rate from local to general anesthesia being as high as 6.3% and showed that local anesthesia was associated with significantly shorter procedure time and in‐hospital stay. Ehret et al suggested that local anesthesia is associated with favorable effects such as a reduced need for inotropic support and packed red blood cells transfusions. Having gained enough experience in the field of TAVI, it was possible to reduce the rate of general anesthesia to below 8%.…”
Section: Discussionmentioning
confidence: 99%
“…Fröhlich et al in a meta‐analysis described the conversion rate from local to general anesthesia being as high as 6.3% and showed that local anesthesia was associated with significantly shorter procedure time and in‐hospital stay. Ehret et al suggested that local anesthesia is associated with favorable effects such as a reduced need for inotropic support and packed red blood cells transfusions. Having gained enough experience in the field of TAVI, it was possible to reduce the rate of general anesthesia to below 8%.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis published in the same year, with 19 studies, showed no differences between the two anesthetic techniques (RR: 0.91; 95%CI 0.70-1.18; p=0.48). 25 One-year or long-term survival, as well as procedure-related complications, such as stroke, myocardial infarction, acute kidney injury, vascular and bleeding complications also did not differ between LA/CS and general anesthesia in several studies. 21,26 LA/CS were associated with lower rates of systemic hypertension and subsequent intra and post-procedural inotropic support, and potentially lower pulmonary complications rate, like the incidence of respiratory failure and pneumonia associated with mechanical ventilation.…”
Section: Local Anesthesia/conscious Sedationmentioning
confidence: 92%
“…21,26 LA/CS were associated with lower rates of systemic hypertension and subsequent intra and post-procedural inotropic support, and potentially lower pulmonary complications rate, like the incidence of respiratory failure and pneumonia associated with mechanical ventilation. 22,23 As a result, early recovery after the procedure can be achieved, leading to a shorter length of post-procedural ICU stay and LOS, 12,20,22,25,27 e.g. mean 1.5-2.1 days shorter in LOS under LA/CS than under general anesthesia.…”
Section: Local Anesthesia/conscious Sedationmentioning
confidence: 99%
See 2 more Smart Citations